Secure sensor information management and mining. - Thuraisingham, B. (IEEE Signal processing magazine)
This article describes issues and challenges for secure sensor information management. In particular, we discuss data management for sensor information systems including stream data management, distributed data management for sensor data, sensor information management including mining sensor data, security for sensor databases, and dependable sensor information management such as tradeoffs between security, real-time processing, and fault tolerance. Finally we discuss object-based infrastructures for sensor systems as well as directions for sensor information management.